2019
DOI: 10.14740/jcs383
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Radius Ewing’s Sarcoma Resection Followed by Migration of the Proximal Radius: Report of Two Cases

Abstract: We present two young patients who developed Ewing's sarcoma in the proximal radius, managed surgically by resection and no reconstruction with K-wire fixation of the distal radioulnar joint for 6 weeks. Following surgery, both patients developed proximal radius migration with subluxation, which caused the patients to complain about deformation. Proximal radius migration with subluxation is well documented in trauma cases, although they were not described in orthopedic oncology since reconstruction was the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…To our knowledge, there are limited reported cases in the literature regarding proximal radius migration, subluxation, or wrist pain after proximal radius resection without reconstruction [18] . Al-Juhani W et al reported two cases of proximal radius migration following resection of radial head for Ewing sarcoma [18] . Liu et al reported a high rate of complications with en bloc resection of giant cell tumors of the radius [19] .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are limited reported cases in the literature regarding proximal radius migration, subluxation, or wrist pain after proximal radius resection without reconstruction [18] . Al-Juhani W et al reported two cases of proximal radius migration following resection of radial head for Ewing sarcoma [18] . Liu et al reported a high rate of complications with en bloc resection of giant cell tumors of the radius [19] .…”
Section: Discussionmentioning
confidence: 99%